PENERAPAN DAN IMPLEMENTASI ANGGARAN BERBASIS KINERJA - Isti'anah Isti'anah (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
Good governance is an effort to change government behavior to be professional, accountability, and participation. Reform of the budget system is needed to support good governance. The Performance Based Budgeting obligates each ministry or agency reconstructs clearly about mission, vision and strategy.